Patient Reported Outcome Analysis after Posterior Decompression and Posterolateral Fusion Surgery in Lumbar Degenerative Spondylolisthesis - Paudel, Prakash; Shah, Damber Bikram; Joshi, Sumit; Karki, Prasanna; Budhathoki, Samip Jung; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2020)
Introduction: Lumbar degenerative spondylolisthesis is an acquired slippage of a vertebra due to degenerative arthritis of the facet joints without any defect in the vertebral ring. Degenerative spondylolisthesis is commonly treated with posterior decompression and posterolateral fusion. This study aims to evaluate the clinical outcome of posterior decompression and instrumented posterolateral fusion surgery by analysing patient reported outcome measures. Materials and Methods: A retrospective study in which patients who had posterior decompression and instrumented posterolateral fusion for lumbar degenerative spondylolisthesis between September 2017 and August 2019 at Nepal Mediciti Hospital were included in the study. Other types of spondylolisthesis managed with similar technique and patients who had follow up period of less than three months were excluded. Functional outcome was assessed by comparing pre and post-operative patient reported outcome measures: VAS leg pain, VAS back pain and Oswestry Disability Index (ODI). The paired t-test was used for statistical analysis. Results: Of the 16 patients, 81.25% were female. Mean age and mean follow up period were 58.81± 10.47 years and 13.56±7.15 months respectively. Seventy five percent had grade I spondylolisthesis. Most common level of spondylolisthesis was L4/5 (62.5%). Fourteen patients reported improvement in their symptoms after surgery. The changes in functional outcome scores between baseline and at follow up evaluation were as follows: 32.70 ± 17.44 points for ODI, 3 ±1.89 for VAS leg pain, and 5.37 ± 2.36 for VAS back pain (P<0.001). Superficial wound infection was the most common complication observed in 18.3%. Conclusion: In our case series, 87.5% had improvement in their symptoms after surgery. The change in mean score of patients’ reported outcome measures before and after surgery was statistically significant. We recommend a prospective comparative study between decompression alone and the fusion technique for the evaluation of long term functional outcome.